2015
DOI: 10.1371/journal.pone.0122396
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Transcriptome and Whole Genomic Resequencing Data to Identify Key Genes Affecting Swine Fat Deposition

Abstract: Fat deposition is highly correlated with the growth, meat quality, reproductive performance and immunity of pigs. Fatty acid synthesis takes place mainly in the adipose tissue of pigs; therefore, in this study, a high-throughput massively parallel sequencing approach was used to generate adipose tissue transcriptomes from two groups of Songliao black pigs that had opposite backfat thickness phenotypes. The total number of paired-end reads produced for each sample was in the range of 39.29–49.36 millions. Appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…By constructing three mouse models with adipocyte (AC)-speci cally attenuated in ammatory responses, Asterholm et al [22] showed that proper AT remodeling and expansion are executed by in ammatory responses at the level of ACs, so that reduced or impaired local in ammatory responses in the AC cause pathogenic obesity-related conditions, such as hepatic steatosis or metabolic dysfunction due to ectopic lipid accumulation [23,24]. Interestingly, a recent AT-derived RNA-seq analysis of pigs showed that pigs with thicker backfat tended to express signi cantly lower levels of immune and in ammatory genes than pigs with thinner back fat, which indicates that expression of high in ammatory genes may be associated with lower fat accumulation in AT [25]. Few studies have addressed the positive role of the in ammatory response which may have a role in fat deposition in lean individuals, although fat cell differentiation and fat deposition must be regulated appropriately to maintain healthy fat homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…By constructing three mouse models with adipocyte (AC)-speci cally attenuated in ammatory responses, Asterholm et al [22] showed that proper AT remodeling and expansion are executed by in ammatory responses at the level of ACs, so that reduced or impaired local in ammatory responses in the AC cause pathogenic obesity-related conditions, such as hepatic steatosis or metabolic dysfunction due to ectopic lipid accumulation [23,24]. Interestingly, a recent AT-derived RNA-seq analysis of pigs showed that pigs with thicker backfat tended to express signi cantly lower levels of immune and in ammatory genes than pigs with thinner back fat, which indicates that expression of high in ammatory genes may be associated with lower fat accumulation in AT [25]. Few studies have addressed the positive role of the in ammatory response which may have a role in fat deposition in lean individuals, although fat cell differentiation and fat deposition must be regulated appropriately to maintain healthy fat homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Baranova et al (2005) reported a paradoxical decrease in the expression of pro-angiogenic genes, which is another gene class that is expected to increase in obese individuals [29]. Moreover, a recent AT-derived RNA-seq analysis of pigs showed that pigs with thicker back fat tend to express signi cantly lower levels of immune and in ammatory genes than pigs with thinner back fat, indicating that the expression of high in ammatory genes may be associated with lower fat accumulation in AT [30].…”
Section: Introductionmentioning
confidence: 99%
“…Pigs have long served as models in biomedical research because of their similarity to humans with regard to body size, physiological conditions, eating patterns, and fat deposition [1][2][3][4]. Pig breeds do vary in fat deposition and are characterized by differences in intramuscular fat content and backfat thickness.…”
Section: Introductionmentioning
confidence: 99%